Concentration and source analysis of polycyclic aromatic hydrocarbons in PM2.5 during heating period in Yantai City - Tiantian ZHANG; Ying WANG; Zhiyu WANG; Tianran ZHANG; Wenna GUO; Songsong WANG; Xiaoyu ZHANG (环境与职业医学)
BackgroundPolycyclic aromatic hydrocarbons (PAHs) are widely known atmospheric pollutants, which can cause serious harm to human body and ecological environment. ObjectiveTo analyze the concentrations and sources of PAHs in atmospheric PM2.5 in Zhifu District and Longkou City during the heating period in Yantai. MethodsTwo monitoring sites in Zhifu District and Longkou City of Yantai were selected, and PM2.5 sample collection was carried out from April 2023 to March 2024. Gas chromatography-mass spectrometry was applied to analyze the concentrations of PAHs in atmospheric PM2.5 during the heating period (from November 2023 to March 2024) and the non-heating period (from April to October 2023). The concentrations of PAHs in the two periods were compared and the sources of PAHs during the heating period were analyzed by characteristic ratio method. ResultsDuring the heating period, the total concentration ranges of PAHs in atmospheric PM2.5 at the monitoring sites in Zhifu District and Longkou City of Yantai were (1.59-23.70) ng·m−3 and (2.08-149.72) ng·m−3 respectively, and the medians (M) and the 25th and 75th percentiles (P25, P75) were 4.99 (2.61, 8.09) ng·m−3 and 15.46 (8.15, 29.05) ng·m−3 respectively. The PAHs concentrations in Longkou City were significantly higher than those in Zhifu District in all months (P<0.05). The highest median total concentrations of PAHs in both sites were reported in January (8.14 ng·m−3 and 81.56 ng·m−3 respectively). In the non-heating period, the M (P25, P75) of the total PAHs concentrations at the two sites were 1.59 (1.59, 2.78) ng·m−3 and 4.11 (2.94, 7.97) ng·m−3 respectively, much lower than those in the heating period (P<0.01). The order of composition of PAHs by ring number in PM2.5 at both sites was 4-ring> 5-ring> 6-ring, with the 4-ring contributing the largest proportion (65.33% and 46.39% respectively). Fluoranthene had the highest concentration among PAHs at both sites, with concentrations M (P25, P75) of 1.29 (0.51, 1.78) ng·m−3 and 2.32 (1.30, 3.82) ng·m−3 respectively. The characteristic ratios of fluoranthene/(fluoranthene + pyrene), fluoranthene/pyrene, benzo[a]anthracene/(benzo[a]anthracene + chrysene), pyrene/benzo[a]pyrene, benzo[a]pyrene/(benzo[a]pyrene + chrysene), benzo[a]pyrene/benzo[g,h,i]pyrene, and indeno[1,2,3-c,d]pyrene/(indeno[1,2,3-c,d]pyrene + benzo[g,h,i]pyrene) in Zhifu District were 0.62, 1.65, 0.41, 4.48, 0.50, 0.93 and 0.47 respectively, and those in Longkou were 0.57, 1.35, 0.40, 2.89, 0.29, 0.79 and 0.47 respectively. The results showed that PAHs pollutants were generated by combination of coal combustion, vehicle exhaust emissions and gasoline combustion. ConclusionDuring the heating period in Yantai area, the total concentration of PAHs in atmospheric PM2.5 is significantly higher than that in the non-heating period. Among them, during the heating period, the pollution level in Longkou City is significantly higher than that in Zhifu District. The local PAHs may be sourced from mixed pollution, and the main sources include gasoline, and coal combustion and vehicle exhaust emissions.